Using big data to improve the quality of healthcare in the Jordanian medical sector - Okour, Dr. Karim Saeed (The journal of contemporary issues in business and government, 2019)
This study aimed here to reveal the extent and extent of using some operating hospitals located in Jordan of modern electronic business technologies from big data with the aim of improving and developing health care in their hospitals. The study was applied to that random sample of operating hospitals in JORDAN, whose size reached (45) hospitals The design has not been determined. For collecting data, it has been used with descriptive statistics, and those tests aim to analyze the data and make hypothesis testing such as the signal test, Mann-Whitney test and test. The study finally reached a number of results, the most important of which were: The decrease in the size and level of adoption of these technologies and big data in the Jordanian governmental hospitals affiliated with the Ministry of Health and the private hospitals operating in the Amman region, Whereas, the size of these systems and technologies in the governmental and private hospitals of the Jordanian Ministry of Health was between medium and high. The study also found here that there is such a relationship between the independent variables (such as type of hospital, hospital size, hospital age, obtaining accreditation).